Pemberdayaan Petani Kedelai Hitam di Sumbermulyo, Bambanglipuro, Bantul, Melalui Peran Corporate Social Responsibility PT.Unilever Indonesia Tbk. - , RARA AYENDA, Krisdyatmiko, S.Sos, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Empowerment of black soybean farmers is one of the programs run by PT. Unilever Indonesia Tbk as part of Corporate Social Responsibility ( CSR ). Today, the meaning of Corporate Social Responsibility is not just limited to collecting corporate profits, given that business ethics are more to profit, people and planet that supported the Triple Bottom Line. One form of CSR undertaken by PT. Unilever Indonesia Tbk is a partnership that is done through the empowerment of black soybean farmers. The method used in this research is descriptive qualitative method of analysis. This method, combined with the use of purposive and snowball to get informants associated with the partnership PT. Unilever Indonesia Tbk. Data were obtained from a single informant, and triangulated with other informants corroborated with field observations to obtain a high validity. This research was conducted in two Padukuhan, namely Padukuhan Siten and Plumbungan contained in Sumbermulyo Village, District Bambanglipuro, Bantul. This area is an agricultural area with the majority of people who work as farmers. Agriculturists - planting farmers have knowledge and a good harvest for generations and are ready to partner , this will be the capital for the community in collaboration with the company. In practice, PT. Unilever Indonesia Tbk that has formed Unilever Indonesia Foundation also solicit cooperation with the Foundation Persada and seed experts from the Faculty of Agriculture, Gadjah Mada University. The experts in this type of soybean seeds called Malika black. Bango soy sauce as the main ingredient, then entrusted to Malika black soybean farmers as planting stock with regular coaching by experts seeds and Unilever Indonesia Foundation. Empowerment is done to improve the knowledge of the black soybean planting method is good and right to be able to produce the seeds are ready to be sent to Malika PT. Unilever Indonesia Tbk. As with the Faculty of Agriculture, Unilever Indonesia Foundation with the Foundation Persada more engaged in the empowerment of women farmers. The foundation has established a group of grading which is part of a partnership firm. Sorting is a sorting activity of black soybeans to meet safety standards PT. Unilever Indonesia Tbk. So far, empowerment conducted by Persada Foundation has been able to build the confidence and knowledge of women farmers through the art of dance, theater, to manufacture a sheet of paper. Completing the Foundation also has given the empowerment that women farmers were able to increase the domestic economy through business groups. Carroll reveals there are four stairs CSR to assess the extent to which a company's social responsibility . The first is maximizing profit, obey the law, be ethical, and be a good citizen. PT. Unilever Indonesia Tbk is a company that is on the ladder maximizing profit, meaning the company is still binding as the producer of black soybean farmers remain firm for the sake of boosting the economy. Should, community empowerment is the ability to enrich the community ranging from asset and access. Although PT. Unilever has given Malika as capital to farmers, but the farmers are not equipped to sell their harvest tissue Malika freely.